Developing an Open Access, Competency‐Based Global Oral Health Curriculum: A Global Health Starter Kit. Issue 2 (11th February 2020) - Lambert, R. Frederick; Yu, Amy; Simon, Lisa; Cho, Janice G.; Barrow, Jane; Seymour, Brittany
Abstract: Dental education has seen increases in global health and international educational experiences in many dental schools' curricula. In response, the Consortium of Universities for Global Health's Global Oral Health Interest Group aims to develop readily available, open access resources for competency‐based global oral health teaching and learning. The aim of this study was to develop and evaluate a Global Health Starter Kit (GHSK), an interdisciplinary, competency‐based, open access curriculum for dental faculty members who wish to teach global oral health in their courses. Phase I (2012‐17) evaluated longitudinal outcomes from two Harvard School of Dental Medicine pilot global health courses with 32 advanced and 34 predoctoral dental students. In Phase II (2018), the Phase I outcomes informed development, implementation, and evaluation of the open access GHSK (45 enrollees) written by an interdisciplinary, international team of 13 content experts and consisting of five modules: Global Trends, Global Goals, Back to Basics: Primary Care, Social Determinants and Risks, and Ethics and Sustainability. In Phase III (summer and fall 2018), five additional pilot institutions (two U.S. dental schools, one U.S. dental hygiene program, and two dental schools in low‐ and middle‐income countries) participated in an early adoption of the GHSK curriculum. The increase in perceived knowledge scores of students enrolled in the pilot global health courses was similar to those enrolled in the GHSK, suggesting the kit educated students as well or better in nearly all categories than prior course materials. This study found the GHSK led to improvements in learning in the short term and may also contribute to long‐term career planning and decision making by providing competency‐based global health education.